"Imagined Outcomes": Contrasting Patterns of Opportunity, Capability, and Innovation in British Musical Instrument Manufacturing, 1930–1985. (30th July 2018) - BLUNDEL, RICHARD K.; SMITH, DAVID J.
Abstract : By the mid-twentieth century in the United Kingdom, musical instrument manufacturing had become an increasingly mechanized activity. Craft skills had been displaced in many areas, yet remained a vital source of competitive advantage in local and international markets and were particularly valued by professional musicians. This article examines the contrasting experiences of two British musical instrument manufacturers, tracing the unfolding relationship between their pursuit of entrepreneurial opportunities and capability development. Boosey & Hawkes, a large, well-established manufacturing and publishing company, was an early pioneer, while Paxman Bros., a small musical retailer, transformed itself into one of the world's most respected specialist manufacturers. The narrative probes the factors that shaped decision making in these companies as they developed a series of design innovations for one of the more complex brass instruments: the French horn. It draws on relevant theoretical insights to examine how a dynamic interaction between opportunity and capability, coupled with unanticipated contingencies, contributed to divergent outcomes for each company.